Plants species, perception and intangible benefits of the vegetation of ramna park, Dhaka - Uddin, AHM Mezbah; Shomrat, Abulais; Alfasane , Mohammed Almujaddade; Uddin, Mohammad Zashim (Bangladesh Journal of Botany, 2024)
The study concerns with the evaluation of the current status of plant species composition and also perceptions and views of visitors on intangible vegetation benefits of Ramna Park, which focuses on determining the evaluation of the park in terms of physical/natural characters, accessibility, surroundings, motive for use, and the significance and quality of an urban green space in a megacity. A total of 384 people participated in a questionnaire composed of closed and open-ended questions. The study identified a total of 352 plant species under 96 families from the park area. The percentage of native and exotic species was found here at 49 and 51%, respectively. Based on people’s perceptions, the study revealed that Ramna Park was more valued for its accessibility, green space characteristics, conservation, and importance of greenery in city dwellers daily lives. Among the participants, 41% visited the park for walking and relaxation, followed by 17% for physical exercise. In addition, regarding the participant’s overall perceptions of intangible urban vegetation benefits, 48% of people were satisfied in terms of planning, 77% were satisfied with the current greenery, and 38% were satisfied with current security. Moreover, 52% of people were not able to identify the plants in the park area, and 84% of people could not distinguish the plants between native and exotic. Most of the participants (97%) mentioned the need for more parks and demanded parks having native plants with improved maintenance and proper administration throughout the city. Visitor’s opinions revealed that the support was realized for the importance and management strategies of Ramna Park as it facilitates socialization, leisure, recreation, and physical activities. Recommendations include promoting the dominance of native species, replacing exotics gradually, increasing the number of wildlife supporting species, enhancing public awareness, and integrating expert opinion into urban plantation programs. Bangladesh J. Bot. 53(4): 1011-1020, 2024 (December)